CPD Program - Rahman, Md. Tahminur (Anwer Khan Modern Medical College Journal, 2013)
Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 56 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16946